The multi‐faceted regulation of nuclear tRNA gene transcription. Issue 8 (26th June 2019) - Hummel, Guillaume; Warren, Jessica; Drouard, Laurence
Abstract: Transfer RNAs are among the most ancient molecules of life on earth. Beyond their crucial role in protein synthesis as carriers of amino acids, they are also important players in a plethora of other biological processes. Many debates in term of biogenesis, regulation and function persist around these fascinating non‐coding RNAs. Our review focuses on the first step of their biogenesis in eukaryotes, i.e. their transcription from nuclear genes. Numerous and complementary ways have emerged during evolution to regulate transfer RNA gene transcription. Here, we will summarize the different actors implicated in this process: cis ‐elements, trans ‐factors, genomic contexts, epigenetic environments and finally three‐dimensional organization of nuclear genomes. © 2019 IUBMB Life, 2019 © 2019 IUBMB Life, 71(8):1099–1108, 2019